The feasibility of the virtually delivered dementia lifestyle intervention for getting healthy together (DELIGHT) program for people living with dementia and their family/friend care partners - Olivia L. Tupling; Bobby Neudorf; Sevana Haghverdian; Heather H. Keller; Carrie McAiney; Laura E. Middleton (PLoS ONE, 2025)
Background Improving supports to enhance quality of life for people living with dementia is a priority of research and practice. The DEmentia Lifestyle Intervention Program for Getting Healthy Together (DELIGHT) was co-designed by people with dementia, care partners, community stakeholders, and researchers with the goal of promoting ‘living well’ with dementia. Objective A mixed methods study design was used to assess the feasibility of the 8-week virtual DELIGHT program, which incorporates group exercise and shared learning on topics related to health and wellbeing. Methods Feasibility was evaluated through recruitment rate, attendance, and retention, along with semi-structured interviews that probed the program impact and recommended changes. Interviews were transcribed and analyzed using thematic analysis. Quality of life, physical activity, balance confidence, exercise self-efficacy, nutrition risk, social connection, balance, and strength were also assessed pre- and post-program. Results A total of 19 participants were recruited to the two virtual program offerings (average of 4.75 participants/month). Of these, 17 (89.5%) completed the pre- and post-program evaluations. Average attendance was 78% demonstrating feasibility of the program. Four themes related to the impact of and satisfaction with the DELIGHT program were identified: Creating and Strengthening Connections described the sense of community felt among participants and study leaders, Sharing Knowledge and Learning described participants enjoyment in learning from one another and sharing their own valuable knowledge, Motivation to Improve Health and Wellbeing described improvements in participants’ functional abilities and motivation to continue healthy habits beyond the program, and Providing Hope and Challenging Stigma described a mindset shift to believing in the possibility of living well with dementia and challenging stigma. Conclusion DELIGHT is a feasible lifestyle intervention for people living with dementia and their care partners. Further research to evaluate the feasibility of the in-person DELIGHT program and the effectiveness of both in-person and virtual offerings is warranted.